THEAPPLICATION OF RESEARCH BASED LEARNING (RBL) MODEL BASED ON CHARACTER EDUCATION TO IMPROVE NATURAL SCIENCE LEARNING AT THE FIFTH GRADE OF ELEMENTARY SCHOOL - Maulyda, Bintang (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract: TheApplication Of Research Based Learning (Rbl) Model Based On Character Education To Improve Natural Science Learning At The Fifth Grade Of Elementary School. The objectives of this research are: (1)to describe the application of Research Based Learning (RBL) model based on character education to improve Natural Science learning; (2)to improve Natural Science learning based on Character Education. This research is a collaborative Class Action Research (CAR) that was conducted in three cycles. The subjects of this research were fifth grade students of SDN 3 Selang in the academic year of 2014/2015, totaling 29 students consisting of 11 male students and 18 female students. The result show that the application of Research Based Learning (RBL) Model Based Character Learningcan increase Natural Science learning.   Keywords: RBL, character learning, Natural Science   Abstrak: Penerapan Model Research Based Learning (RBL) Berbasis Pendidikan Karakter untuk Meningkatkan Pembelajaran IPA di Kelas V SD. Tujuan penelitian ini yaitu: (1) untuk mendeskripsikan penerapan model Research Based Learning (RBL) Berbasis Pendidikan Karakter dalam peningkatan pembelajaran IPA; (2) untuk meningkatkan hasil belajar IPA melalui penerapan model Research Based Learning (RBL) Berbasis Pendidikan Karakter. Penelitian ini merupakan Penelitian Tindakan Kelas (PTK) yang dilaksanakan dalam tiga siklus. Subjek penelitian ini adalah siswa kelas V SDN 3 Selang tahun ajaran 2014/2015 yang berjumlah 29 siswa yang terdiri dari 11 siswa laki-laki dan 18 siswa perempuan. Hasil penelitian menunjukkan bahwa penerapan model research based learning berbasisi pendidikan karakter dapat meningkatkan pembelajaran IPA di kelas V SD.   Kata kunci: RBL, pendidikan karakter, IPA